Localized synovial sarcoma of the foot or ankle: A series of 32 Cooperative Weichteilsarkom Study Group patients. Issue 1 (13th November 2018) - Scheer, Monika; Greulich, Michael; Loff, Steffan; Vokuhl, Christian; Feuchtgruber, Simone; von Kalle, Thekla; Münter, Marc; Stegmaier, Sabine; Sparber‐Sauer, Monika; Kazanowska, Bernarda; Niggli, Felix; Fuchs, Jörg; et al.
Abstract : Background: Synovial sarcoma of the foot/ankle is rare. Mutilating surgery is often discussed. Methods: Patients registered from 1981 to 2013 were analyzed. Cooperative Weichteilsarkom Studiengruppe (CWS) protocols recommend chemotherapy for all synovial sarcoma patients. Results: Thirty‐two of 330 patients with localized synovial sarcoma had their tumor at the foot/ankle. Eleven of thirty‐two tumors were >5 cm. Twenty were T1, 11 T2, and one TX, respectively. Eight (25%) patients underwent primary complete resection with free margins (Intergroup Rhabdomyosarcoma Study [IRS] I), 12 of 32 (38%) primary complete resection with positive margins (IRS II), and 12 of 32 (38%) had macroscopic residuals (IRS III). The best surgical result at any time was R0 in 19, R1 in 10 and R2 in one patient, and missing in two. Mutilation was documented in 14 of 32 (44%). Radiotherapy was conducted in 20 patients. All patients achieved a first complete remission. Five‐year‐event‐free survival and overall survival rates were 80% and 86%, respectively. Four patients suffered local and four other metastatic recurrences. IRS and the best surgical result at any time did not correlate with survival. There was no prognostic difference between R0‐ and R1‐resection. Conclusion: Survival expectancies for patients with localized synovial sarcomas of the foot/ankle compare favorably to that of those with other affected sites. Discussion: Further studies are needed to set the limits of minimally required aggressiveness of local therapies.